2017
DOI: 10.3390/su9122238
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of the Distribution of Small Businesses in the Eastern Villages of Gilan Province with Emphasis on the Tourism Sector in Mountainous Regions

Abstract: Abstract:The development of small businesses in rural areas as a key strategy for sustaining the population and improving the quality of life of villagers has always been a concern for many developed and developing countries. Some rural areas provide their villagers with favorable conditions for the development of businesses in order to enjoy the potential in the field of tourism. Sustainable development in these areas can be achieved with systematic attention and planning. In the present work, the spatial ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
1
7
0
1
Order By: Relevance
“…The results showed that using spatially weighted regression method is more suitable than classical regression methods in the hedonic pricing models where the spatial impacts are considered to be higher. These results are consistent with the studies in the literature (Latinopoulos, 2018; Kostakis and Theodoropoulou, 2017;Hajilo et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results showed that using spatially weighted regression method is more suitable than classical regression methods in the hedonic pricing models where the spatial impacts are considered to be higher. These results are consistent with the studies in the literature (Latinopoulos, 2018; Kostakis and Theodoropoulou, 2017;Hajilo et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…He suggests a tourism spatial structure by using strategies to optimize China's tourist location (Wang et al, 2018). Hajilo et al (2017) examined the spatial analysis of the distribution of small facilities in the eastern part of the Ghilan province by underlining the tourism in mountainous areas. And finally, they have found that the distribution of the facilities for all kinds of activities is much higher in plains and valleys compared to the hills and mountainous areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the form of tourism economic spatial organization, Hajilo et al [28] analyzed the spatial distribution characteristics of tourism enterprises in the eastern part of Gilan Province. Shih [16] empirically tested a sample of drive tourists taken from 16 destinations in Nantou, Taiwan, and analyzed the structural characteristics of their network locations on different tourism routes.…”
Section: Network Analysis In Tourism Economic Cooperationmentioning
confidence: 99%
“…In general, the contribution of entrepreneurship to economic development has been documented both in developing and developed countries [2]. The development of small businesses in rural areas has been particularly recognized as a key strategy to improve rural livelihoods [3]. Entrepreneurship enables local communities to use local resources as tourism products that provide socio-economic benefits to their communities [2].…”
Section: Introductionmentioning
confidence: 99%
“…Entrepreneurship enables local communities to use local resources as tourism products that provide socio-economic benefits to their communities [2]. Entrepreneurial engagement in small tourism businesses has the potential to contribute to social, economic, and environmental outcomes for local communities by offering sustainable solutions to job creation, provision of goods and services, and preservation of natural resources [3,4]. Tourism empowers local communities, where empowerment is a multidimensional concept that includes economic, social, political, and psychological empowerment [5][6][7].…”
Section: Introductionmentioning
confidence: 99%